2009
DOI: 10.1111/j.1538-7836.2009.03585.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between hirudin and citrate in monitoring the inhibitory effects of P2Y12 receptor antagonists with different platelet function tests

Abstract: To cite this article: Pittens CACM, Bouman HJ, van Werkum JW, ten Berg JM, Hackeng CM. Comparison between hirudin and citrate in monitoring the inhibitory effects of P2Y12 receptor antagonists with different platelet function tests. J Thromb Haemost 2009; 7: 1929-32. Dual treatment with aspirin and clopidogrel is currently the therapy of choice in the prevention of recurrent cardiovascular events following coronary stent implantation. However, not all patients benefit equally from this antiplatelet regimen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…However, by chelating calcium, citrate reduces the free calcium levels in the blood samples thus interfering with the platelet aggregation process. Previous studies have reported a potential underestimation of the %IPA of P2Y 12 inhibitors due to higher platelet aggregation values obtained in citrate than with other anticoagulants [25]. The selection of optimal doses of P2Y 12 inhibitors to be tested during clinical development is based on targeting %IPA values between 70 and 90 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by chelating calcium, citrate reduces the free calcium levels in the blood samples thus interfering with the platelet aggregation process. Previous studies have reported a potential underestimation of the %IPA of P2Y 12 inhibitors due to higher platelet aggregation values obtained in citrate than with other anticoagulants [25]. The selection of optimal doses of P2Y 12 inhibitors to be tested during clinical development is based on targeting %IPA values between 70 and 90 %.…”
Section: Discussionmentioning
confidence: 99%
“…By chelating calcium, citrate reduces the free calcium levels in the samples and interferes with the platelet aggregation processes. Napsagatran is a direct thrombin inhibitor and prevents blood coagulation without affecting free calcium levels [25,26].…”
Section: Pharmacodynamic Assessmentsmentioning
confidence: 99%
“…Mean aggregation values for heparin and hirudin were significantly different from citrate, though they did not differ from one another in aggregation (Figure 2). Again, this could be due to the calcium-chelating effects of citrate [17], which are not observed with heparin or hirudin. This was further supported by the observation that mean AUC for heparin and hirudin were not significantly different from one another.…”
Section: Discussionmentioning
confidence: 99%
“…The performance characteristics of this product have not been established.) This new test cartridge is intended to measure the effect of clopidogrel on platelet function [38].…”
Section: Clinical Utilitymentioning
confidence: 99%